Chronic kidney disease-mineral bone disorder. (2nd December 2019) - Cronin, Thomas; Abdelmahamoud, Mohammed; Falls, Derek; Punshon, Katherine; Willows, Jamie; Mordi-Blair, Nony
Abstract : Chronic kidney disease-mineral bone disorder is typically seen in patients with advanced chronic kidney disease. It is managed primarily by renal physicians, but non-renal physicians are also likely to encounter patients undergoing treatment for this condition in both inpatient and outpatient settings so a basic understanding of the principles may be helpful. This article covers the fundamentals of the pathophysiology, diagnosis and treatment of chronic kidney disease-mineral bone disorder.